The Early Dynastic "Maison des Fruits" at Tell K in Tello (Ĝirsu) - Tsouparopoulou, Christina (Bulletin of ASOR, 2024)
Taking as a point of departure a foundation figurine of the 3rd-millennium Early Dynastic Lagashite ruler Ur-Nanše, housed in the National Archaeological Museum of Athens, Greece, this article presents a revised understanding of the "Maison des Fruits" and Tell K at Tello/Ĝirsu. It is centered on the objects and their inscriptions unearthed in and associated with the Maison, includes relevant parallel structures and objects, and concludes with a discussion of the function of the Maison. It is suggested that this was a sacred building closely related to water and fish and leaves open the discussion regarding to whom this structure was dedicated.